Microtus arvalis - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Microtus arvalis (Pallas, 1778). Nova Spec. Quad. Glir. Ord., p. 78. TYPE LOCALITY: Germany, no exact locality; neotype from U.S. S. R., R.S.F.S. R., Leningrad Obi. DISTRIBUTION: France and N. Spain east through Europe and Siberia to the upper Yenesei River; south to N. Turkey, Caucasus, Lake Balkash, Sinkiang (China) (SW), and Altai Mtns.; isolates in Guernsey and Orkney Isis. COMMENT: Subgenus Microtus; see Anderson, 1960, Univ. Kans. Publ. Mus. Nat. Hist., 12: 181 -216. Includes ilaeus; see Meier and Yatsenko, 1980, Zool. Zh., 59(2):283-288, who used kirgisorum for what was formerly known as ilaeus; "ilaeus” (now kirgisorum) was considered distinct by Corbet, 1978: 114, on the basis of evidence of hybrid sterility, also see Meier, 1976, Trans. I Inti. Theriol. Congr., 1:400-401; see also comment under kirgisorum. Includes orcadensis; see Corbet, 1961, Nature (Lond.), 191: 1037-1040. Includes igmanensis; see Zivkovic et al., 1975, Arh. Biol. Nauka, 26:123- 134, and Corbet, 1978:113. The status of igmanensis needs further clarification (SRL); see also comment under epiroticus. Type locality of neotype fixed by Meier et al., 1972, Zool. Zh., 51: 157- 161. ISIS NUMBER: 5301410008080002001 as M. arvalis. 5301410008080033001 as M. orcadensis. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 4), pp. 477-504 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 490, DOI: 10.5281/zenodo.7353034